Evidence for cutaneous dysbiosis in dystrophic epidermolysis bullosa. (1st October 2021) - Bar, J.; Sarig, O.; Lotan‐Pompan, M.; Dassa, B.; Miodovnik, M.; Weinberger, A.; Sprecher, E.; Segal, E.; Samuelov, L.
Summary: Background: The human microbiome project addresses the relationship between bacterial flora and the human host, in both healthy and diseased conditions. The skin is an ecosystem with multiple niches, each featuring unique physiological conditions and thus hosting different bacterial populations. The skin microbiome has been implicated in the pathogenesis of many dermatoses. Given the role of dysbiosis in the pathogenesis of inflammation, which is prominent in dystrophic epidermolysis bullosa (DEB), we undertook a study on the skin microbiome. Aim: To characterize the skin microbiome in a series of patients with DEB. Methods: This was a case–control study of eight patients with DEB and nine control cases enrolled between June 2017 and November 2018. The skin of patients with DEB was sampled at three different sites: untreated wound, perilesional skin and normal‐appearing (uninvolved) skin. Normal skin on the forearm was sampled from age‐matched healthy controls (HCs). We used a dedicated DNA extraction protocol to isolate microbial DNA, which was then analysed using next‐generation microbial 16S rRNA sequencing. Data were analysed using a series of advanced bioinformatics tools. Results: The wounds, perilesional and uninvolved skin of patients with DEB demonstrated reduced bacterial diversity compared with HCs, with the flora in DEB wounds being the least diverse. We found an increased prevalence of staphylococci species in the lesional and perilesional skin of patients with DEB, compared with their uninvolved, intact skin. Similarly, the uninvolved skin of patients with DEB displayed increased staphylococcal content and significantly different microbiome diversities (other than staphylococci) compared with HC skin. Conclusions: These findings suggest the existence of a unique DEB‐associated skin microbiome signature, which could be targeted by specific pathogen‐directed therapies. Moreover, altering the skin microbiome with increasing colonization of bacteria associated with nonchronic wounds may potentially facilitate wound healing in patients with DEB.